2000
DOI: 10.1107/s010827010000500x
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric aqua(glutarato)(hydrogen glutarato)lanthanum(III) monohydrate

Abstract: The structure of the title compound, [La(C5H6O4)(C5H7O4)‐(H2O)]·H2O, consists of dense layers formed by chains of one‐edge‐sharing LaO9(H2O) polyhedra, linked together by the glutarate ligand. The three‐dimensional polymeric structure, built up through connection of these layers by the hydrogen glutarate ligand, exhibits cavities accommodating a guest water mol­ecule. The lanthanum ion is tenfold coordinated by four glutarates, acting as bridging–chelating carboxyl­ate groups, by three hydrogen glutarates, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Although it was generally found that an increase in reaction temperature favors anhydrous compounds formation, the two isostructural crystals 1 and 2 , obtained hydrothermally, contain water molecules, whereas 3 resulting from soft chemical route at room temperature is completely anhydrous. Moreover, the partially deprotonated ligand appeared to depend roughly on the metal ligand ratio and probably on reaction time [18,20,25,37]. As shown in a comparative study in the series of α,ω-aliphatic dicarboxylic acids [16,17,18,19,20,21,22,23,24,25,26,37], the optimal hydrogen bonding patterns should be more determining in the deprotonation of these acids than their corresponding pKa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was generally found that an increase in reaction temperature favors anhydrous compounds formation, the two isostructural crystals 1 and 2 , obtained hydrothermally, contain water molecules, whereas 3 resulting from soft chemical route at room temperature is completely anhydrous. Moreover, the partially deprotonated ligand appeared to depend roughly on the metal ligand ratio and probably on reaction time [18,20,25,37]. As shown in a comparative study in the series of α,ω-aliphatic dicarboxylic acids [16,17,18,19,20,21,22,23,24,25,26,37], the optimal hydrogen bonding patterns should be more determining in the deprotonation of these acids than their corresponding pKa.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the partially deprotonated ligand appeared to depend roughly on the metal ligand ratio and probably on reaction time [18,20,25,37]. As shown in a comparative study in the series of α,ω-aliphatic dicarboxylic acids [16,17,18,19,20,21,22,23,24,25,26,37], the optimal hydrogen bonding patterns should be more determining in the deprotonation of these acids than their corresponding pKa. The nature of alkali salts used as starting materials has probably a great effect on the formation of this kind of material, through the pH value of the mixture [38,39,40,41,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly notable for the bridging groups which appear as syn,anti bridges while in those related 1D compounds [12,13] one oxygen atom is simultaneously involved in a syn,syn chelate and in a syn,anti bridge. Moreover, this structural aspect exhibited by one carboxylato oxygen atom is repeatedly found in all the remaining known 2- [14] and 3D [15][16][17][18][19][20][21] lanthanide-organic materials containing glutaric acid residues, thus rendering the present compound the first example of a glutaratolanthanide material in which an inter-lanthanide bridge via a carboxylato group is enforced by a syn,anti bridge. Apart from structurally creating the aforementioned bimetallic units, the glutarato anionic residues further establish physi- (Figure 1, c and d).…”
Section: Crystal Structure Description Of [Sm(glu)(pic)(h 2 O) 2 ]mentioning
confidence: 88%
“…As reported by Zhang et al [13] for the 1D 2 ] molecular tape present in the crystal structure also contains, external to the glu/Sm core, chelating aromatic organic ligands (picolinato residues) which seem to prevent the growth of the hybrid polymer in more than one direction by removing available coordination sites in the metallic centres (Figure 1). Indeed for all known and related compounds, when these chelating moieties are not present, 2- [14] and 3D [15][16][17][18][19][20][21][22] materials are typically isolated. The picolinic acid residues appear coordinated to the Sm 3+ metallic centres in a typical N,O-chelating fashion (Scheme 1) with a bite angle of 64.97(10)°, a value consistent with those reported for similar compounds [23][24][25][26] (10 entries in the CSD, with values spanning from 60.5 to 67.6°; median of 64.0°).…”
Section: Crystal Structure Description Of [Sm(glu)(pic)(h 2 O) 2 ]mentioning
confidence: 99%
See 1 more Smart Citation